Determinant of entrepreneurial intention among middle school students / Nurul Aqila Azmi and Nur Hidayah Mokhtar - Azmi, Nurul Aqila; Mokhtar, Nur Hidayah (Faculty of Business and Management, 2016)
The study aims to explore the determinants of entrepreneurial intention among middle school students by studying the importance of entrepreneurship education in order to discover necessary knowledge and skills for improving middle school students. Besides, student involvements in entrepreneurship activities are believed to enhance entrepreneurial intention. This research also focused on four elements that can give impacts toward entrepreneurial intention. First element is perceived educational support, second is perceived relational support, third is personal attitude and lastly perceived behavior control. Adopting judgmental sampling method, the data were then collected by using five Likert Scale and 150 questionnaires were distributed o middle school students between the age of 13 to 17 years old. The result showed that entrepreneur intention of middle school students is influenced by perceived behavior control, personal attitude, perceived relational support and perceived educational support. This research is expected to contributed better understanding for middle school students toward entrepreneurial intention where it has also proven that seminar programs by educational institutions may increase entrepreneurship development.